Pregunta
upstudy study bank question image url

\( 6 x-y-4=0 \) and \( 9 x+1=-2 y \)

Ask by Gray Savage. in South Africa
Feb 20,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\( x=\frac{1}{3} \) and \( y=-2 \).

Solución

Solve the system of equations \( 6x-y-4=0;9x+1=-2y \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}6x-y-4=0\\9x+1=-2y\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}y=6x-4\\9x+1=-2y\end{array}\right.\) - step2: Substitute the value of \(y:\) \(9x+1=-2\left(6x-4\right)\) - step3: Expand the expression: \(9x+1=-12x+8\) - step4: Move the expression to the left side: \(9x+12x=8-1\) - step5: Add and subtract: \(21x=8-1\) - step6: Add and subtract: \(21x=7\) - step7: Divide both sides: \(\frac{21x}{21}=\frac{7}{21}\) - step8: Divide the numbers: \(x=\frac{1}{3}\) - step9: Substitute the value of \(x:\) \(y=6\times \frac{1}{3}-4\) - step10: Substitute back: \(y=6\times 3^{-1}-4\) - step11: Calculate: \(y=-2\) - step12: Calculate: \(\left\{ \begin{array}{l}x=\frac{1}{3}\\y=-2\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=\frac{1}{3}\\y=-2\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(\frac{1}{3},-2\right)\) The solution to the system of equations \(6x-y-4=0\) and \(9x+1=-2y\) is \(x=\frac{1}{3}\) and \(y=-2\).

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To solve the equations \( 6x - y - 4 = 0 \) and \( 9x + 1 = -2y \), let's first rearrange them into a more convenient form for solving. The first equation can be rewritten as \( y = 6x - 4 \). For the second equation, rearranging gives \( 2y = -9x - 1 \) or \( y = -\frac{9}{2}x - \frac{1}{2} \). Now we set the right-hand sides equal to each other: \( 6x - 4 = -\frac{9}{2}x - \frac{1}{2} \). Multiplying everything by 2 to eliminate the fraction yields: \( 12x - 8 = -9x - 1 \). Adding \( 9x \) to both sides gives: \( 21x - 8 = -1 \). Adding 8 to both sides results in \( 21x = 7 \), thus \( x = \frac{1}{3} \). Substituting \( x \) back into the first equation to find \( y \): \( y = 6\left(\frac{1}{3}\right) - 4 = 2 - 4 = -2 \). So the solution for the equations is \( x = \frac{1}{3} \) and \( y = -2 \). Enjoy checking the solution by substituting back into both original equations!

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad